Research on the Cultivation of the Digital Economy Ecosystem in China and Indonesia Under the Background of the Belt and Road Initiative - Yuning, Xiong; Zehao, Fu; Xin, Yang; Siyuan, Xu; Shiqin , Tang (Published by Confucius Institute UNS, 2000)
The development of the digital economy in Indonesia and China cannot be separated from the construction of the ecosystem. The current design of the digital economy ecosystem mainly revolves around policy guidance, production collaboration and infrastructure, but the focus of digital economy development in Indonesia and China is different. Through policy features and comparative analysis, as interviews with Indonesian enterprises and consumers, this paper identifies the problems in the development of China's digital economy ecosystem in Indonesia and proposes countermeasures based on market guidance, policy support, new economy, infrastructure development and public governance, with a view to providing useful references for the development of the digital economy ecosystem in China and Indonesia.